Blue rose-inspired approach towards highly graphitic carbons for efficient electrocatalytic water splitting. (September 2019) - Zhou, Binghan; Zhang, Mingchao; He, Wenya; Wang, Haomin; Jian, Muqiang; Zhang, Yingying
Abstract: Heteroatom doping in inert carbon matrixes has been widely adopted for efficient carbonaceous electrocatalysts. However, typical doping methods such as magnetic agitation and mechanical stirring may lead to a bad dispersion and thus poor reproducibility for electrocatalysis. Here, we proposed a strategy guided by the Murray's law to obtain hierarchically porous and highly graphitic carbons by cultivating rose flower in Ni(NO3 )2 solution and pyrolyzing Ni-doped rose petals. The efficient Murray's network in the rose petals promotes uniform and sufficient transfer and absorption of Ni 2+ ions, which later serve as catalyst sites for highly graphitic carbons at high temperature. Because of the enhanced crystallinity of carbon that promotes the smooth transfer of electrons and the uniformly embedded Ni nanoparticles in the carbon matrix that serve as electrocatalytic active sites, the as-obtained carbons show superior performance as a bi-functional electrocatalyst for efficient overall water splitting. Graphical abstract: Image 1